2011
DOI: 10.1111/j.1525-1446.2010.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Web‐delivered Education on Preceptor Role Self‐Efficacy and Knowledge in Public Health Nurses

Abstract: Web-delivered continuing education targeted to public health nurse preceptors is an effective method to increase confidence and knowledge for the preceptor role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 21 publications
3
41
0
1
Order By: Relevance
“…[19] Nurses gain knowledge, have an opportunity to provide feedback, evaluate new nurses in a more appropriate manner, and prepare preceptors for their role. The findings of this review are similar to the findings of Larsen et al [3] and Smedley et al [20] who noted an increase in nurses' knowledge about preceptorship after completing preceptorship programs. Nurses' knowledge is improved through continuous education and organizational support.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…[19] Nurses gain knowledge, have an opportunity to provide feedback, evaluate new nurses in a more appropriate manner, and prepare preceptors for their role. The findings of this review are similar to the findings of Larsen et al [3] and Smedley et al [20] who noted an increase in nurses' knowledge about preceptorship after completing preceptorship programs. Nurses' knowledge is improved through continuous education and organizational support.…”
Section: Discussionsupporting
confidence: 77%
“…[21] This will offer the best opportunity to promote safe, timely, effective, and efficient patient care. In a study conducted in hospital that utilizing preceptors (n = 31) in the United States, [3] it was found that preceptorship programs were associated with improved self- efficiency at both immediate and 3-month post-test and increased knowledge at immediate post-test only. Self-efficacy was described by Smedley et al [20] as the way that nurses perceived themselves and their abilities to act in the role of preceptors.…”
Section: Knowledge Of Preceptormentioning
confidence: 99%
See 2 more Smart Citations
“…Formal training of preceptors is mostly non-existent and the training that occurs is haphazardly done (Larsen & Zahner, 2011;Mulder & Uys, 2012;Troxel, 2009;Zilembo & Monterosso, 2008). It is also evident that a good clinician is not necessarily a good preceptor (Ortman, Mann, & Arsenault, 2010;Troxel, 2009).…”
Section: Introductionmentioning
confidence: 99%